The Effect of Corporate Tax Avoidance on the Level of Corporate Cash Holdings: Evidence from Indonesian Public Listed Companies - Muhammad Irham Kurniawan; Siti Nuryanah (Australasian Accounting, Business and Finance Journal, 2017)
This study aims to examine the effect of corporate tax avoidance to the corporate cash holdings. Recent tax avoidance research found that tax avoidance is able to facilitate managerial rent extraction in the form of transfer of resources owned by the company. This study attempts to test how the relationship of tax avoidance with the amount of cash held by the company. The sample consists of 46 non-financial, non-property, non-real estate and non-construction companies from 2009-2016, with a total 368 observations. The study uses two different cash holdings measures to test the robustness of the research results. This study cannot find evidence that tax avoidance have a significant relationship to the level of cash holdings in public companies in Indonesia. Both measurements of cash holdings gave the same conclusions to the results of the study. This study provides an insight that agency theory in the context of tax avoidance and corporate cash holdings in developing countries such as Indonesia needs to be explored further as the agency conflict in Indonesia as a developing country is more principal-principal conflicts.
Keywords: Tax avoidance; cash holdings; corporate finance; Indonesia